Echocardiographic evaluation of working dogs of the Military Police of Rio de Janeiro: effects of the breed and body weight - Alex Moreira de Lima; Rodrigo Mencalha Moreira; Marcelo Salvador Gomes; Marcia Torres Ramos; Carlos Augusto dos Santos-Sousa; Paulo Souza-Júnior; Marcelo Abidu-Figueiredo (Brazilian Journal of Veterinary Medicine, 2022)
The Military Police of Rio de Janeiro state use dogs as a decisive tool for patrol and detection of drugs, weapons, and explosives. Complementary tests, such as echocardiography, are essential to maintain the integrity of these animals. This study aimed to evaluate the echocardiographic parameters of the working dogs belonging to the Military Police of Rio de Janeiro and compare them with the available data. Echocardiographic evaluation was performed on 48 healthy adult dogs from the Canine Action Battalion of the Military Police of Rio de Janeiro, Brazil. The sample consisted of 13 Labrador Retrievers, 12 Malinois Belgian Shepherds, 10 German Shepherds, 8 Dobermann Pinschers, and 5 Dutch Shepherds. Echocardiographic variables were correlated with body weight (BW). A positive correlation (P=0.0142, r=0.6837) between BW and the diameter of the left atrium was found in Malinois Belgian Shepherds. In German Shepherds, a positive correlation between BW and the internal diameter of the right ventricle during diastole (P=0.0320, r=0.6757) was observed; in addition, a positive correlation between BW and left ventricular internal diameter (P=0.0344, r=0.6689) during diastole was also found. Echocardiographic evaluations of these working dogs differed slightly from those previously established for similar-sized dog breeds.